Pengaruh Pengeluaran Pemerintah Bidang Pendidikan, Gender Gap dan Pendapatan Per Kapita Terhadap Ketimpangan Pendidikan dan Ketimpangan Pendapatan Kabupaten/Kota di Provinsi Kalimantan Barat - Hamzah, Fahrur; Rosyadi, Rosyadi; Kartika, Metasari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
This study aims to analyze the impact of government expenditures, gender gap and per capita income on the education and income inequalities of regencies and cities in West Kalimantan Province. This research used secondary data in a form of data panel. These data include time series data for 5 years (2011 "“ 2015) and cross-section data for 14 regencies and cities in West Kalimantan Province. The results showed that the government expenditures and per capita income have significant negative effect on the education inequality. In contrary, gender gap give insignificant positive effect on the education inequality. Furthermore, the education inequality has a significant positive effect on the income inequality.